Aspek Pertumbuhan Ikan Lemuru (Sardinella lemuru) Yang Didaratkan di Pelabuhan Perikanan Nusantara (PPN) Pengambengan, Bali - Annisa, Kindy Nurrani; Restu, I Wayan; Pratiwi, Made Ayu (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
The growth aspect is important for the preparation of fish resource management because fish conditions can be described by the growth data. This study was conducted to examine aspects of the growth of Lemuru fish landed in PPN Pengambengan in the period of October-December 2019, as input in the preparation of a sustainable management plan for Lemuru fisheries. Data analysis was including growth patterns, length distribution, age groups, and growth parameters. The results of the analysis on the growth aspects obtained Lemuru Fish growth patterns are positive allometric, meaning that the proportion of energy from food is allocated maximally by Lemuru Fish for weight growth. The distribution of Lemuru fork length ranges from 115-196.3 mm with the mode found in the 155.7 mm, this means that Lemuru fish are in the adult stage. This stock is growing, marked by 2 age groups with 2 shifts of the age group towards the right. Asymptotic length of Lemuru Fish has decreased, this condition is thought to be the impact of overfishing.